Quando a cidade encontra o rio, o rio se perde: Goiânia e o rio Meia Ponte (1933-2020) - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The Meia Ponte River is one of the main rivers in the State of Goiás and about 50% of the population of Goiás lives in its hydrographic basin. This river played a fundamental role in the construction of the new capital of Goiás, known as the “capital of the interland”, and represented a symbol of the arrival of modernity in the Midwest. Thus, the objective of this dissertation is to analyze the relationship between the city of Goiânia and the Meia Ponte river from its construction in the 1930s to the present day. The analysis goes through the relevance of the river in the initial project, the consequences arising from the growth of the city, as well as the lack of public protection policies for this important source. In this sense, the hypothesis raised is that this river, over the decades has become a victim of degradation, neglect and abandonment both by the population of Goiás, as well as by the managers and public policies that should protect it. The analysis has as a theoretical reference the perspective of Environmental History, privileging interdisciplinarity and conceiving human relations and interactions with the environment as inseparable. The study dialogues with an extensive bibliography dealing with the new capital and its main sources are newspapers, urban projects in Goiânia and official decrees. Thus, it is clear that despite being constantly in the capital's media due to floods or scarcity of water, pollution and the consequent bad smell, the river that could be synonymous with well-being has become “invisible” to the people of Goiás.
When the city meets the river, the river is lost: Goiânia and the river meia ponte (1933-2020)
Keywords: Meia Ponte; Goiânia; História Ambiental; Degradação; Meia Ponte; Goiânia; Environmental History; Degradation; CIENCIAS HUMANAS::HISTORIA; ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS